New species and a new record of Entomobryinae (Collembola, Entomobryomorpha) from Amurskaya Region (the Far East of Russia) - Baquero, Enrique; Potapov, Mikhail; Jordana, Rafael (Zootaxa, 2021)
The studied area (Far East of Russia) is very little investigated for the Entomobryidae family. A specific sampling in the area has made it possible to detect the presence of four and one new species of the genera Entomobrya and Willowsia respectively, which are herein described (E. amurica sp. nov., E. mediostriata sp. nov., E. umbroviolacea sp. nov., E. bicincta sp. nov. and W. babykinae sp. nov.) from the western part of the Far East of Russia. Homidia hjesanica is also recorded.